ANALISA PARAMETER FREKUENSI PADA PENGUJIAN DAN KALIBRASI ELEKTROSTIMULATOR - Nur Hadziqoh; Romi Mulyadi; Nani Lasiyah; Muddasir Muddasir (Al Tamimi Kesmas: Jurnal Ilmu Kesehatan Masyarakat (Journal of Public Health Sciences), 2023)
An electrostimulator is a device that produces millions of tiny electrical signals that enter the body through an electrode that is placed on the surface of the skin near the affected area or above it. Electrostimulators are widely used to determine the response of nerve and muscle cells to certain electrical stimuli. In this study, the process of analyzing the frequency parameters in the testing and calibration of the electrostimulator was carried out in which the calibration was aimed to find out some deviations between the calibrated tool and the calibrator. The method used is the work method that has been determined by the Ministry of Health of the Republic of Indonesia, which includes physical inspection and tool functions, electrical safety and frequency measurement performance testing. For the results of this study on physical examination and tool function by 10%, for electrical safety checks the value obtained is 40%, performance testing is 50%.